Bihar Second Five Year Plan - Planning Commission (Planning Commission)
The Constitution lays down the goal for the country. the directive principles of State policy which govern both the State and the Central Governments require that their activity should directed to promote though welfare of the people by securing and protecting, a effectively as they may, a social order in which justice, social, economic and political shall inform all the institutions of the national life.
Bihar